2019
DOI: 10.3389/fimmu.2019.02293
|View full text |Cite
|
Sign up to set email alerts
|

WNT/β-Catenin Signaling Pathway Regulating T Cell-Inflammation in the Tumor Microenvironment

Abstract: Immunotherapy with checkpoint inhibitors has greatly prolonged the overall survival of cancer patients in melanoma and many other cancer types. However, only a subset of patients shows clinical responses from these interventions, which was predicated by the T cell-inflamed tumor microenvironment. T cell-inflamed phenotype is characterized by the infiltration of CD8+ T cells, CD8α/CD103-lineage dendritic cells (DCs), as well as high density of forkhead box P3 (FoxP3)+ regulatory T cells (Tregs) that are associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
159
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(174 citation statements)
references
References 100 publications
2
159
0
Order By: Relevance
“…Another WNT regulator is Leucine-rich repeat-containing Gprotein-coupled receptor 5 (LGR5), a protein that binds to the R-spondin ligand family members (RSPO) and maintains WNT signaling through the neutralization of the RNF43/ZNF3 ligases ( Figure 1A) (36,37,54,55). YAP/TAZ are also WNT regulators and compete with LRP5/6 for the same binding domain of AXIN.…”
Section: Modulators Of Wnt Signaling: Rnf43/znrf3 Rspo Yap/taz Andmentioning
confidence: 99%
“…Another WNT regulator is Leucine-rich repeat-containing Gprotein-coupled receptor 5 (LGR5), a protein that binds to the R-spondin ligand family members (RSPO) and maintains WNT signaling through the neutralization of the RNF43/ZNF3 ligases ( Figure 1A) (36,37,54,55). YAP/TAZ are also WNT regulators and compete with LRP5/6 for the same binding domain of AXIN.…”
Section: Modulators Of Wnt Signaling: Rnf43/znrf3 Rspo Yap/taz Andmentioning
confidence: 99%
“…Finally, we focused on the effects of molecular pathways; according to the results of the GSEA, terms for bile acid metabolism, downregulation of K-ras signaling, and WNT/β-catenin pathways were highly enriched in the MSI-S2 subgroup of the three cohorts. Some studies suggested that the WNT/ β-catenin pathway could promote tumor intrinsic resistance to immune checkpoint inhibitors [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies are beginning to provide insights into the mechanisms by which Wnt signaling cascade directly modulates immunological functions of other immune cells, such as macrophages, myeloid-derived suppressor cells (MDSCs), Tregs, CD4 + T cells, CD8 + T cells, and NK cells (71). There are several excellent studies and reviews that discuss extensively how the Wnt signaling pathway shape the functions of other immune cells (43,44,60,71,72) and will thus be discussed only briefly ( Table 1). Tumor-infiltrating T cells express markedly higher levels of Wnt3a and β-catenin, and display dysfunctional and exhausted effector memory phenotype (28).…”
Section: Effects Of Wnts In Modulating Functions Of Other Immune Cellmentioning
confidence: 99%
“…Treatment of mice with established B16-OVA tumors or EL4-OVA tumors with IWP-L6 or C59 delayed tumor growth, and this was due to marked increase in tumor-antigen-specific CD4 + and CD8 + effector T cells with reduced number of Tregs, IL-10 + Tr1, and IL-10 + CD8 T cells within the tumors (21). Furthermore, IWP-L6 or C59 treatment enhances the ability of DCs to capture and cross-present tumor antigens to CD8 + T cells (71). Similar effect was observed in murine models of melanoma, colorectal, and ovarian cancer using different POCRN inhibitors, RXC004 and WNT974 (82).…”
Section: Blocking Fzd-lrp5/6 Signalingmentioning
confidence: 99%